1988
DOI: 10.2118/13171-pa
|View full text |Cite
|
Sign up to set email alerts
|

Role of Asphaltenes in Compositional Grading of a Reservoir's Fluid Column

Abstract: The relationship between compositional variations induced by gravity and reservoir-fluid phase behavior has been investigated. In light oils (stock-tank oil gravity ::::;0.85 g/cm 3 [2=:35°API]), strong compositional grading will occur if the reservoir fluid is near critical. In heavier oils, compositional grading is caused by the segregation of asphaltenes, resulting in variation in oil viscosity and the possibility of tar-mat formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 8 publications
0
64
0
Order By: Relevance
“…Dahl and Speers, 1986;Karlsen et al, 1995;Leythaeuser and Rückheim, 1989;Tissot and Welte, 1984). A number of studies, devoted to understanding the reasons and consequences of diversities in petroleum composition, have already been undertaken long ago (Bailey et al, 1973a;Bailey et al, 1973b;Dahl and Speers, 1986;Espach and Fry, 1951;Evans et al, 1971;Hirschberg, 1988;Hunt, 1979;Justwan and Dahl, 2005;Karlsen et al, 1995;Karlsen and Skeie, 2006;Milner et al, 1977;Sage and Lacey, 1939;Tissot and Welte, 1984;Tyson, 1995). These studies have revealed that the factors that cause heterogeneities in petroleum composition in reservoirs can roughly be related to 1) variations in source rock organic facies and source rock maturity and 2) secondary alteration processes.…”
Section: 2mentioning
confidence: 99%
“…Dahl and Speers, 1986;Karlsen et al, 1995;Leythaeuser and Rückheim, 1989;Tissot and Welte, 1984). A number of studies, devoted to understanding the reasons and consequences of diversities in petroleum composition, have already been undertaken long ago (Bailey et al, 1973a;Bailey et al, 1973b;Dahl and Speers, 1986;Espach and Fry, 1951;Evans et al, 1971;Hirschberg, 1988;Hunt, 1979;Justwan and Dahl, 2005;Karlsen et al, 1995;Karlsen and Skeie, 2006;Milner et al, 1977;Sage and Lacey, 1939;Tissot and Welte, 1984;Tyson, 1995). These studies have revealed that the factors that cause heterogeneities in petroleum composition in reservoirs can roughly be related to 1) variations in source rock organic facies and source rock maturity and 2) secondary alteration processes.…”
Section: 2mentioning
confidence: 99%
“…While reservoir temperature and pressure gradients are mentioned as the main causes of compositional grading, but this phenomenon is not limited to these factors (Hoier and Whitson 2000). In addition to the gravity segregation (Montel and Gouel 1985), thermal diffusion (Danesh 1998) and thermal convection (Saidi 1987;Ghorayeb and Firoozabadi 2000) which are affected by variations of temperature and pressure, other factors such as incomplete equilibrium distribution and immigration of hydrocarbons, presence of a dynamic aquifer in contact with a part of reservoir, asphaltene precipitation (Hirschberg 1988), heterogeneity of reservoir structure due to faults, variety of hydrocarbon distribution (such as paraffin and aromatic) in plus fraction (Danesh 1998;Schulte 1980) and biological degradation were cited in several publications (Ross and Farrimond 2010;Huang et al 2004;Larter and Wilhelmsb 2003). From a thermodynamic point of view, compositional grading models could be classified into two categories of equilibrium and non-equilibrium thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In Ghawar field, for example, the tar zone extends more than 25 km and reaches up to 150 m in thickness [5]. According to several geochemical studies presented by various researchers, tar mats form due to water washing, natural deasphalting, biodegradation, and gravity segregation, which results in grade variations in the composition with changes in depth [2,6].…”
Section: Introductionmentioning
confidence: 99%